History of the Gothic : Gothic literature, 1825-1914 - Killeen, Jarlath, 1976- (Gothic literary studies., 2009)
This volume in this exciting new series provides a detailed yet accessible study of Gothic literature in the nineteenth century. It examines how themes and trends associated with the early Gothic novels were diffused widely in many different genres in the Victorian period, including the ghost story, the detective story and the adventure story.